Persepsi Konsumen Terhadap Promosi Pada Aplikasi “FISDOK” Solusi Smart Pelayanan Kesehatan: Study kasus: Desa Banjarsari, Kecamatan Gajah, Kabupaten Demak - Yane Puspito Sari (Yayasan Literasi Sains Indonesia, 2022)
Promotion is one of the factors that influence purchasing decisions. Promotion is an important factor that must be done by a company. With promotion, a company can provide information to consumers about the products it creates. The advantages of these products can be known by consumers through promotions and can generate interest in consumers to buy these products. Promotion is a communication activity carried out by a company to explain to consumers about the products created by the company. Promotion is a variety of ways to inform, persuade, and remind consumers directly or indirectly about a product or brand being sold. The problems discussed are limited to consumer perceptions of promotions in the